Management skills for clinicians. - LaGanga, Linda R. (Healthcare management collection., 2019)
This book introduces new managers working in health care to the basic skills and competencies to support them in transitioning to their managerial roles. Some topics and examples also can help more experienced managers reassess and revitalize their skills. Targeted readers have been promoted recently into managerial, supervisory positions. They have clinical training and experience, and little or no business management training and experience. More experienced managers can benefit, too, from collected insights of other managers who were interviewed and from examples in recent and revisited literature. The book covers both"hard" business skills and "soft" people/organizational skills. We draw from books, articles, examples and managerial experience of the author and colleagues at different organizational levels and throughout health care settings and professions.